Development of the neural processing of vocal emotion during the first year of life. Issue 3 (3rd April 2021) - Zhao, Chen; Schiessl, Ingo; Wan, Ming Wai; Chronaki, Georgia; Abel, Kathryn M.
ABSTRACT: Human infants are "wired" to respond to social information, an important capacity for survival. The ability to discriminate vocal emotion in others is likely to play a key role in successful social interactions with caregivers, which facilitate the rapid social-communicative development that infants typically undergo in the latter half of their first year. Infants have voice-sensitive brain regions that have been shown previously to be responsive to emotional prosody by 7 months. This study aimed to investigate the developmental trajectory of vocal emotion processing in temporal regions using functional near-infrared spectroscopy (fNIRS) to measure brain sensitivity to angry, happy, and neutral vocalizations in the same infant at 6, 9, and 12 months. We found significant and increasing temporal cortical activation in response to vocal emotional stimuli over the three time points, suggesting consistent enhanced responses for happy compared to angry vocalizations, and vocal anger sensitivity is developing incrementally. The findings suggest that the neural processing of angry and happy prosody may follow distinct developmental pathways and is gradually "tuned" to become specialized between 6 and 12 months. This first longitudinal study of vocal emotion brain processing between 6 and 12 months highlights the need for more research to understand what drives typical and atypical social cognitive development across infancy and for follow-up into the second year.